2022
DOI: 10.3390/ijms23179808
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic and Metabolic Impairments in Induced Pluripotent Stem Cell-Derived Cardiomyocytes Generated from Duchenne Muscular Dystrophy Patients

Abstract: Duchenne muscular dystrophy (DMD) is caused by mutations in the dystrophin gene and dilated cardiomyopathy (DCM) is a major cause of morbidity and mortality in DMD patients. We tested the hypothesis that DCM is caused by metabolic impairments by employing induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) generated from four DMD patients; an adult male, an adult female, a 7-year-old (7y) male and a 13-year-old (13y) male, all compared to two healthy volunteers. To test the hypothesis, we measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The reshaped distribution and the reduced number of mitochondria in DMD hiPSC-derived cardiac fibroblasts blunted mitochondrial respiration, which was further confirmed by the lower expression of ETC complexes. A recent study reported impaired energy metabolism as well as abnormal mitochondrial structure and function in iPSC-derived cardiomyocytes generated from adult DMD patients, but not from a young DMD patient [ 28 ]. Similarly, mitochondrial function and biogenesis were found compromised in cardiomyocytes from the Duchenne mouse model mdx with “humanized” telomeres [ 29 ] suggesting that mitochondrial dysfunction accompanies dystrophin loss and may account for the etiology of dystrophic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…The reshaped distribution and the reduced number of mitochondria in DMD hiPSC-derived cardiac fibroblasts blunted mitochondrial respiration, which was further confirmed by the lower expression of ETC complexes. A recent study reported impaired energy metabolism as well as abnormal mitochondrial structure and function in iPSC-derived cardiomyocytes generated from adult DMD patients, but not from a young DMD patient [ 28 ]. Similarly, mitochondrial function and biogenesis were found compromised in cardiomyocytes from the Duchenne mouse model mdx with “humanized” telomeres [ 29 ] suggesting that mitochondrial dysfunction accompanies dystrophin loss and may account for the etiology of dystrophic heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…This is also accompanied by an increase in the respiratory activity of organelles, which is noted in mdx mice [171,175]. In the case of young DMD patients, a healthy-like metabolic status and mitochondrial respiratory activity was also found [176]. However, in later stages, model animals and DMD patients show a significant decrease in mitochondrial function, which is also accompanied by abnormal organelle morphology [179].…”
Section: Contribution Of Sr and Mitochondrial Channels To The Develop...mentioning
confidence: 94%
“…Indeed, skeletal muscle mitochondria of mdx mice show a decrease in the efficiency of oxidative phosphorylation and ATP synthesis [167,168,177,178,181,205], which is accompanied by a change in the level of electron transport chain (ETC) complexes and the efficiency of their functioning, as well as a decrease in the membrane potential of organelles (Figure 2) [168,177,178,181,205]. A decrease in the efficiency of ATP synthesis is also shown on biopsy specimens of DMD patients [176,183]. Dystrophin-deficient animals also show a reduction in some important mitochondrial inner membrane exchangers and, in particular, ANT1, which is responsible for the release of ATP from mitochondria in exchange for ADP [159,167].…”
Section: Contribution Of Sr and Mitochondrial Channels To The Develop...mentioning
confidence: 94%
See 1 more Smart Citation
“…While no study has performed functional assessments of cardiac mitochondrial oxidative phosphorylation in people with DMD, one study found iPSC-derived cardiomyocytes from adults with DMD had significant reductions oxygen consumption coupled to ATP synthesis (Willi et al, 2022). Attenuations in the phosphocreatine (PCr) energy system indicated by lower PCr concentrations were also observed in these cells (Willi et al, 2022).…”
Section: Oxidative Phosphorylation and Substrate Catabolismmentioning
confidence: 99%